2000
DOI: 10.1258/1357633001935635
|View full text |Cite
|
Sign up to set email alerts
|

Distance education for health centre staff in rural Japan

Abstract: We have evaluated a course delivered by videoconferencing to rural health centre staff in Hokkaido. The course focused on the planning and evaluation of community health interventions. It included four 90 min sessions and two follow-up sessions. Fourteen professional staff members (public health nurses, nutritionists and dental assistants) attended each class. Knowledge of community health-care planning and evaluation was higher at post-education testing than pre-education testing. Ratings for 'using a compute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Several distance learning approaches are also being explored in Japan dental education [31]. Various projects improving learning environment by using ICT have been adopted by the Ministry of Education.…”
Section: Meeting Current and Future Challenges In Dental Education Inmentioning
confidence: 99%
“…Several distance learning approaches are also being explored in Japan dental education [31]. Various projects improving learning environment by using ICT have been adopted by the Ministry of Education.…”
Section: Meeting Current and Future Challenges In Dental Education Inmentioning
confidence: 99%
“…22 While some research has already shown that telemedicine provides individuals a platform for learning specific medical techniques, 23,24 telemedicine may also provide the organizations involved with additional opportunities for intense information gathering and related learning. 25,26 The desire to learn from relatively rare events and the ability of telemedicine technology to capture those events in great detail that can be accessed from a remote location may serve to induce some organizations to form telemedicine partnerships or networks for learning purposes. If these rare learning experiences and rich data accumulate over time, they may serve to allow intense learning from telemedical interventions.…”
Section: Learning and Telemedicinementioning
confidence: 99%
“…Positive experiences have been reported regarding the impact of these programmes in different parts of the world 9–13 . One of the most successful of these educational programmes is the Perinatal Continuing Education Programme (PCEP), developed at the University of Virginia between 1975 and 1978 as part of the US National Institutes of Health 14 support of perinatal care regionalisation and education.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] Positive experiences have been reported regarding the impact of these programmes in different parts of the world. [9][10][11][12][13] One of the most successful of these educational programmes is the Perinatal Continuing Education Programme (PCEP), developed at the University of Virginia between 1975 and 1978 as part of the US National Institutes of Health 14 support of perinatal care regionalisation and education. To date, it has been extended to 43 states in the USA, includes almost 200 regional medical centres and a much larger number of smaller community hospitals, and has involved more than 130 000 obstetric and neonatal health care providers.…”
Section: Introductionmentioning
confidence: 99%